Pertumbuhan dan Hasil Dua Belas Genotipe Kacang Hijau pada Beberapa Dosis Pupuk Kandang Sapi di Lahan Ultisol - Andria, Andria; Herison, Catur; Sudjatmiko, Sigit; Dewi, Nurwita (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2016)
One major problem of low mungbean production in Indonesia is the lack of high yielding varieties for marginal land. A study was done with an objective to compare growth and yield of twelve mung bean genotypes on ultisol fertilized with several doses of cow manure. Twelve mung bean genotypes were grown in a field under a randomized complete block design arranged in a Split Plot Design with 3 replications. The Main Plots were four doses of cow manure, i.e. 0, 3, 6 or 9 ton.ha-1 and the Sub-Plots were twelve mungbean genotypes, i.e. VR 3, VR 61, VR 88, VR 200, VR 204 K, VR 213 K, VR 266 ct, VR 341, VR 368, VR 601 m, VR 222 Walet and VR 1074 Vinna-1. The result showed that the interaction between cow manure doses and mungbean genotypes was only occured on number of leaf. Genotype VR 61 demonstrated the highest plant stature, the greatest pod number, the heafiest pod and seeds per plant. Increasing dose of cow manure until 9 tons.ha-1did not reach the optimum level for the growth and yield of mungbean genotypes yet, except on the number of leaf variable on genotype VR 3, VR 88, VR 200, VR 266 ct and VR 601.